Pengaruh Penambahan Pati Biji Durian (Durio zibethinus murr) terhadap Kualitas Kimia dan Organoleptik Bakso Ayam - Yudha Wirawan; Djalal Rosyidi; Eny Sri Widyastuti (Faculty of Animal Science Universitas Brawijaya, 2016)
This research was purposed to find out the effect of durian seed starch addition (DuriozibethinusMurr) on chemical qualities and organoleptic properties of chicken meat balls based on chemical qualities (water content, protein and fat content) and organoleptic properties (texture, smell and taste). The result showed that the treatment P0, P1, P2, P3 gave a very significantly affect (P<0.01) on chemical qualities (water content, protein content, and fat content), gave a significantly affect (P<0.05) on organoleptic properties (texture), but the addition of durian’s seed starch did not give significantly affect (P>0.05) on organoleptic properties (smell and taste). The best result was chicken meatballs made with addition of durian seed starch 15%, it has quality standart that suitable with SNI and acceptable for organoleptic properties. The conclusion of this research was addition of durian’s seed starch in chicken meatballs decreased water content, protein and fat content, also organoleptic properties. The optimum addition of durian’s seed starch on chicken meat balls were 15%.